2013
DOI: 10.1523/jneurosci.0837-13.2013
|View full text |Cite
|
Sign up to set email alerts
|

Leptin Stimulates Neuropeptide Y and Cocaine Amphetamine-Regulated Transcript Coexpressing Neuronal Activity in the Dorsomedial Hypothalamus in Diet-Induced Obese Mice

Abstract: Neuropeptide Y (NPY) neurons in both the arcuate nucleus of the hypothalamus (ARH) and the dorsomedial hypothalamus (DMH) have been implicated in food intake and obesity. However, while ARH NPY is highly expressed in the lean animal, DMH NPY mRNA expression is observed only after diet-induced obesity (DIO). Furthermore, while ARH NPY neurons are inhibited by leptin, the effect of this adipokine on DMH NPY neurons is unknown. In this study we show that in contrast to the consistent expression in the ARH, DMH NP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
48
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(50 citation statements)
references
References 58 publications
(4 reference statements)
2
48
0
Order By: Relevance
“…Human and animal studies suggest that adiposity-induced leptin increase and subsequent leptin resistance would affect these transmitters, causing or worsening asthma symptoms. This relates both to orexigenic neuropeptides such as neuropeptide Y (114)(115)(116)(117)(118)(119)(120) , endocannabinoids (121,122) , endogenous opioids (123)(124)(125)(126) ; and anorexigenic neuropeptides such as tachykinins and its most studied members substance P (127)(128)(129)(130)(131)(132) , α-melanocyte-stimulating hormone (133)(134)(135) , corticotropin-releasing factor (136)(137)(138)(139)(140)(141) and serotonin (142)(143)(144)(145)(146)(147)(148)(149)(150) . Altogether, it suggests that these peptides can modulate asthmatic inflammation among obese patients.…”
Section: Possible Linksmentioning
confidence: 99%
“…Human and animal studies suggest that adiposity-induced leptin increase and subsequent leptin resistance would affect these transmitters, causing or worsening asthma symptoms. This relates both to orexigenic neuropeptides such as neuropeptide Y (114)(115)(116)(117)(118)(119)(120) , endocannabinoids (121,122) , endogenous opioids (123)(124)(125)(126) ; and anorexigenic neuropeptides such as tachykinins and its most studied members substance P (127)(128)(129)(130)(131)(132) , α-melanocyte-stimulating hormone (133)(134)(135) , corticotropin-releasing factor (136)(137)(138)(139)(140)(141) and serotonin (142)(143)(144)(145)(146)(147)(148)(149)(150) . Altogether, it suggests that these peptides can modulate asthmatic inflammation among obese patients.…”
Section: Possible Linksmentioning
confidence: 99%
“…Besides, NPY is expressed in the DMH, and its overexpression is able to induce hyperphagia and obesity [65] , while DMH neurons that lack NPY promote thermogenesis and prevent diet-induced obesity (DIO) [66] . In this sense, leptin's action on the DMH increases the sympathetic tone to BAT, probably by activating NPY in the DMH and contributing to the hypothalamic regulation of thermogenesis [67,68] . Moreover, CART is coexpressed with NPY in chronic obesity; its function seems related to hypothalamic adaptations to increased adiposity and hyperleptinaemia [68] .…”
Section: Hypothalamic Regulation Of Energy Balancementioning
confidence: 99%
“…In this sense, leptin's action on the DMH increases the sympathetic tone to BAT, probably by activating NPY in the DMH and contributing to the hypothalamic regulation of thermogenesis [67,68] . Moreover, CART is coexpressed with NPY in chronic obesity; its function seems related to hypothalamic adaptations to increased adiposity and hyperleptinaemia [68] .…”
Section: Hypothalamic Regulation Of Energy Balancementioning
confidence: 99%
“…43 Interestingly, NPY expression in the DMH is delayed in diet-induced obesity and does not peak until there is a rapid weight gain. 44 As we have examined changes occurring in the first weeks of an HFD, it is possible that the NPY neurons in the DMH may not yet be activated. In support of our findings, it has been shown that in the obese Zucker rat, the presynaptic effects of NPY are attenuated compared with lean littermates.…”
mentioning
confidence: 99%